PERAN PENGAWAS MENELAN OBAT TERHADAP KEPATUHAN MENELAN OBAT PENDERITA TUBERKULOSIS DI KECAMATAN SARUDIK KABUPATEN TAPANULI TENGAH - Faisal; Manalu, Minton (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Tuberculosis is one of ten infectious diseases that cause death in the world. In 2017 the number of new cases of Tuberculosis in Indonesia was 420,994 cases, 1.4 times greater in men than women. The World Health Organization has recommended the Directly Observed Treatment Shortcourse (DOTS) Strategy as a strategy for controlling Tuberculosis. One of the DOTS components developed in Indonesia is the standardization of treatment component with patient supervision and support. Indonesia developed this strategy in the Observed Taking Medication Directly program, a form of monitoring compliance with taking medication according to the program for Tuberculosis sufferers. Medication supervisor who monitors and reminds Tuberculosis sufferers to swallow medicine regularly. Monitoring medication swallowing is very important to accompany sufferers to achieve optimal treatment results. The success of Tuberculosis treatment is an essential performance indicator in evaluating the performance of the national TB control program. The aim of the research was to determine the relationship between medication swallowing supervisors and medication compliance in pulmonary tuberculosis sufferers. This research is a quantitative research with a cross sectional design. The subjects in this research were residents of Sarudik District, Central Tapanuli Regency who were undergoing TB treatment with the DOTS strategy from January 2024 to June 2024, totaling 30 people. The measuring instrument uses a questionnaire sheet and then tested using the chi-square test. The research results showed that 7 respondents (23.3%) did not support the Observed Taking Medication Directly and 23 respondents (76.7%) did not support it. There were 5 respondents (16.7%) who did not comply with taking medication and 25 respondents (83.3%) were compliant with taking medication for TB sufferers. The statistical test results show that there is a significant relationship between the role of the Medicine Supervisor and compliance with taking medicine with a p-value of 0.000 < 0.05; RP= 7.286 with a contingency coefficient (C) of 0.715